2006
DOI: 10.1007/s00223-005-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Daily Physical Education in the School Curriculum in Prepubertal Girls during 1 Year is Followed by an Increase in Bone Mineral Accrual and Bone Width—Data from the Prospective Controlled Malmö Pediatric Osteoporosis Prevention Study

Abstract: The aim of this study was to evaluate a general school-based one-year exercise intervention program in a population-based cohort of girl at Tanner stage I. Fifty-three girls aged 7 to 9 years were included. The school curriculum based exercise intervention program included 40 minutes per school day. Fifty healthy age-matched girls assigned to the general school curriculum of 60 minutes physical activity per week served as controls. Bone mineral content (BMC; g) and areal bone mineral density (aBMD; g/cm 2 ) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(145 citation statements)
references
References 54 publications
8
135
0
2
Order By: Relevance
“…Several previous school based prospective intervention (training) studies have demonstrated that exercise induces positive skeletal effects in pre-pubertal girls (25)(26)(27). These trials have reported 1.5 -29 % greater bone mineral accrual in the intervention groups compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous school based prospective intervention (training) studies have demonstrated that exercise induces positive skeletal effects in pre-pubertal girls (25)(26)(27). These trials have reported 1.5 -29 % greater bone mineral accrual in the intervention groups compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cross-sectional studies have reported higher BMD in physically active compared to physically inactive children (9-11) and a higher BMD in the dominant arm of both tennis and squash players compared with the non-dominant arm (12). Prospective controlled and uncontrolled exercise intervention studies in volunteers (13;14) and in school based exercise interventions, including pre-pubertal and early pubertal children, have reported a higher bone mineral acquisition in the intervention group than in the control group (15)(16)(17)(18)(19)(20). However, all but three (21-23) of these studies have modified the existing physical education curriculum and replaced this with specifically designed bone stimulating activities.…”
Section: Introductionmentioning
confidence: 99%
“…1 The flowchart shows the numbers of articles initially identified and exclusion and inclusion steps. * Randomization unit: I = individual, S = school or class; D = change; These studies provided different data from the same study: Löfgren et al [31] was used for female and male total body, femoral neck, and spine BMC; Linden et al [29] was used for male femoral neck BMD; Valdimarsson et al [50] was used for female spine and femoral neck BMD; NS = not stated; DPA = dual photon absorptiometry, DXA=dual energy x-ray absorptiometry; pQCT = peripheral quantitative computed tomography; BMC = bone mineral content; BA = bone area; aBMD = areal bone mineral density; PHV = peak height velocity; PF = proximal femur; LS = lumbar spine; FN = femoral neck; TB = total body; FA = forearm; TR = trochanter; PC = periosteal circumference; EC = endosteal circumference; Ar = area; CortAr = cortical area; CortThk = cortical thickness; Cort = cortical; Tot = total; vBMD = volumetric bone mineral density; MSCA = muscle crosssectional area; AS!BC = Action Schools! British Columbia.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…3,4 PA exerts significant influence on BMD accrual during growth, 4 which can be categorized into domains (school, leisure and sports). School PA denotes activities performed during school activities, 5,6 while leisure PA denotes activities performed during free time. [7][8][9] Moreover, in young populations, sport PA can itself be considered to be a PA domain.…”
Section: Introductionmentioning
confidence: 99%